Dominance of a macrolide-resistant lineage resulting from capsular switching among group B Streptococcus invasive disease in non-pregnant adults in Portugal (2009–2015). (4th October 2017) - Lopes, Elísia; Fernandes, Tania; Machado, Miguel P; Carriço, João A; Melo-Cristino, Jose; Ramirez, Mario; Martins, Elisabete
Abstract: Background: Lancefield group B streptococci (GBS) are increasing as a cause of invasive disease among non-pregnant adults. We set out to characterize GBS isolated from adults in Portugal in 2009–2015. Methods: All GBS isolates ( n = 555) were serotyped, assigned to clonal complexes (CCs) by multilocus sequence typing and characterized by surface protein and pilus islands (PI) gene profiling. Antimicrobial susceptibility testing was done by disk diffusion and resistance genotypes identified by PCR. High-throughput sequencing of representative isolates was performed. Results: Overall, serotype Ia was the most frequently found in the population (31%), followed by serotypes Ib (24%), V (18%), and III (13%). Serotype Ib increased significantly throughout the study period ( P < 0.001), to become the most frequent serotype after 2013. Over 40% of the isolates belonged to CC1, including most isolates of serotypes Ib ( n = 110) and V ( n = 65), all sharing surface protein gene alp3 and PI-1+PI-2a. Overall erythromycin and clindamicin resistance rates were 35 and 34%, respectively, both increasing throughout 2009–2015 ( P < 0.010). Macrolide resistance was associated with CC1 ( P < 0.001) and serotype Ib ( P < 0.001). Genomic analysis revealed that the Ib/CC1 lineage probably resulted from the acquisition of the type Ib capsular operon in a single large recombination event (≈300 Kb) by a representative of the V/CC1 macrolide-resistant lineage. Conclusion: The serotype Ib/CC1 genetic lineage was detected for the first time and expanded in Portugal in the last 6 years and is now dominant among the GBS population causing invasive disease in adults. Disclosures: J. Melo-Cristino, Pfizer: Grant Investigator, Independent Contractor and Speaker's Bureau, Grant recipient, Research grant and Speaker honorarium. GSK: Grant Investigator and Speaker's Bureau, Grant recipient and Speaker honorarium. Bial: Speaker's Bureau, Speaker honorarium. Novartis: Speaker's Bureau, Speaker honorarium. M. Ramirez, Pfizer: Speaker's Bureau, Speaker honorarium. GSK: Consultant, Consulting fee